The Opportunity of Developing Microalgae Cultivation Techniques in Indonesia - Evi Siti Sofiyah; Iva Yenis Septiariva; I Wayan Koko Suryawan (Research Center for Biology-Indonesian Institute of Sciences, 2021)
The rate of population growth which is relatively rapidly increasing in Indonesia, will require increased fuel. The depletion of the availability of fossil fuels causes the search for the other natural resources needed to become a renewable energy source. One of the significant changes today is microalgae. The application of the algal aquaculture system has been widely applied in the world. The media used in cultivation also varies, one of which is wastewater. The composition of biodiesel energy in Indonesia is increasing and is starting to become the people's choice. Indonesia, which is rich in natural resources, especially the high biodiversity of microalgae, causes microalgae's potential use to be very high. Many studies report the explosion of algal participation in many parts of Indonesia. Research concerning the cultivation of microalgae has been widely successful in Indonesia. The use of microalgae is already available in the field with domestic water treatment applications. The conversion of microalgae into biodiesel also successfully met the requirements of SNI 04-7182-2006.